Eagles, ravens, and other birds of prey: a history of USAF Suppression of Enemy Air Defense doctrine, 1973-1991 - Young, James L., Jr. (Kansas State University, 2018)
During the Cold War, the United States’ foreign policy relied heavily on its ability to project military power. More often than not, the central component of force projection rested on the United States military’s effectiveness in employing air power both by establishing air superiority and through accurate delivery of ordnance. As the primary service tasked with conducting aerial warfare, the United States Air Force (USAF) was expected to maintain this capability either to achieve deterrence or, when necessary, to military action. In January 1973, the USAF seemed incapable of performing the latter task due to the North Vietnamese Integrated Air Defense System’s (NV-IAD’s) effectiveness in Operation Rolling Thunder and its successor, Operation Linebacker. Eighteen years later, Air Force aircraft spearheaded the Coalition’s air attack on the Iraqi Integrated Air Defense System (I-IADS) in January 1991. Considered by many to be the most effective air defense system outside the Soviet Union’s, the I-IADS was expected to exact heavy casualties from the allied forces. Instead, in less than twenty days, the USAF’s dominance was so complete that politicians, analysts and military historians quickly proclaimed a “Revolution in Military Affairs” (RMA). The majority of the current historiography credits advances in precision-guided munitions (PGMs), airframes, and computer technology as the impetus for the RMA. Others have claimed that the USAF’s training methodology and construction of advanced training sites such as the Red Flag complex at Nellis Air Force Base were the primary drivers for the Air Force’s success. While acknowledging the role all of these factors played, this dissertation also demonstrates the key role played by the development of Suppression of Enemy Air Defense (SEAD) doctrine from January 1973 through August 1991. In the aftermath of the American war in Vietnam, the Air Force considered defense suppression a tactical task that was secondary to the primary mission of putting ordnance on target. At the end of Desert Storm, proponents of the Air Force’s SEAD doctrine had convincing evidence that an enemy IADS was not just an ancillary weapons array, but functioned a critical national system just like manufacturing, government, or the people’s will. The process by which this viewpoint changed had effects on the development of the United States Air Force’s Cold War conventional capability in general, and the development of training methods, electronic warfare platforms, and modern airframes specifically.
Keywords: United States Air Force; Suppression of Enemy Air Defense (SEAD); Operation Desert Storm; Wild Weasel; Military doctrine; Cold War military history